Evaluation of Dose-Reduced Direct Oral Anticoagulant Therapy - Barra, Megan E; Fanikos, John; Connors, Jean M; Sylvester, Katelyn W; Piazza, Gregory; Goldhaber, Samuel Z (The American journal of medicine, 2016)
Compared with vitamin K antagonists, direct-acting oral anticoagulants (DOACs) have fixed dosing, limited drug interactions, and do not require therapeutic drug level monitoring. Dose adjustments are recommended for moderate renal dysfunction, low body weight, and select drug interactions. The aim of our study is to determine if DOAC dose reductions were appropriate based on the manufacturer labeling recommendations for each agent. We also followed patients' treatment outcomes. We retrospectively reviewed patients administered a DOAC at a reduced dose between January 2011 and August 2014. The primary outcome was adherence to current manufacturer dose recommendations. The secondary outcome measures were the incidence of thromboembolic events or any bleeding episodes, regardless of severity, while on therapy. Of 224 patients included in the analysis, 43.3% of patients fit criteria for a dose adjustment according to manufacturer recommendations. Only 3 of 28 (10.7%) patients treated with apixaban met 2 out of 3 clinical criteria required for a dose reduction per manufacturer recommendations. Only 54.7% of rivaroxaban-treated patients and 32.2% of dabigatran-treated patients had renal insufficiency requiring a dose reduction. Half of our patient population received aspirin therapy, with 6.3% of patients on triple antithrombotic therapy (dual antiplatelet agents plus an anticoagulant). A past medical history significant for bleeding was prevalent in patients treated with a reduced-dose DOAC (32.1%, 20.4%, and 25.4% of patients in the apixaban-, rivaroxaban-, and dabigatran-treated groups, respectively). Thromboembolic events occurred in 10.7%, 3.6%, and 5.1% of patients in the apixaban, rivaroxaban, and dabigatran groups, respectively. Frequency of bleeding complications, regardless of severity, was 17.9%, 18.2%, and 23.7% of patients in the apixaban, rivaroxaban, and dabigatran groups, respectively. We found that dose-adjusted DOAC therapy was often prescribed in a dose that was lower than package insert recommendations.